On the Spatial Scale Dependence of Long‐Term Persistence in Global Annual Precipitation Data and the Hurst Phenomenon. Issue 4 (10th April 2023) - O'Connell, Enda; O'Donnell, Greg; Koutsoyiannis, Demetris
Abstract: Precipitation deficits are the main physical drivers of droughts across the globe, and their level of persistence can be characterized by the Hurst coefficient H (0.5 < H < 1), with high H indicating strong long‐term persistence (LTP). Previous analyses of point and gridded annual global precipitation datasets have concluded that LTP in precipitation is weak ( H ∼ 0.6) which is inconsistent with higher values of H for large river basins, for example, the Nile. Based on an analysis of gridded annual precipitation data for eight selected regions distributed across the globe, an important new finding is that H increases with the spatial scale of averaging, with mean H values at the grid and regional scale of 0.66 and 0.83, respectively. The discovery of enhanced LTP at the regional scale of averaging of precipitation has important implications for characterizing the severity of regional droughts, as well as LTP in the annual flows of large rivers and recharge to major aquifers. Teleconnections with known modes of low frequency variability in the global climate system are demonstrated using correlation analysis and stepwise regression. Despite having several constituent regions exhibiting LTP, the Northern Hemisphere surprisingly has no LTP; this is shown to result from different modes of low frequency climatic variability canceling each other out. LTP for the Southern Hemisphere is moderate, and weak for Global average precipitation. LTP in Blue Nile basin scale precipitation is shown to explain the Hurst Phenomenon in naturalized annual flows for the River Nile, more than 70 years after its discovery by Hurst. Plain Language Summary: In the 1950s, Harold Edwin Hurst, a British physicist and hydrologist, observed that the annual river Nile flows exhibited long‐term persistence (LTP) where alternating periods of above and below average flows could be unusually long. He characterized LTP using a parameter H which increases from 0.5 (no LTP) up to a limit of 1, and found H of 0.90 for Nile flows. Analyses of long precipitation gauge records have typically given values of H in the range 0.55–0.60, leading some to conclude that precipitation could not account for the stronger LTP in the flows of the Nile and other large rivers. We analyze a long gridded global annual precipitation data set and find that, for eight selected regions, the average value of H increased from 0.66 at the grid scale to 0.83 at the regional scale of averaging. As flows in large rivers result from precipitation gathered over large upstream areas, this explains why the Nile exhibits LTP. Strong LTP at the regional scale is shown to be linked to known long‐term fluctuations in the climate system. Our findings have important implications for characterizing the risks of droughts which can extend over large areas. Key Points: For selected climatic regions, long‐term persistence in gridded annual precipitation data increases with the spatial scale of averaging Long‐term persistence at the regional scale of averaging is linked to large scale modes of fluctuation in the climate system Long‐term persistence in basin average precipitation for the Blue Nile is shown to explain the Hurst Phenomenon for the Nile at Aswan